О некоторых орнаментированных рукописных Евангелиях XVI-XVII веков в собрании М. Тихомирова ГПНТБ СО РАН1 (Библиосфера)
In this article some ornamented gospels belonged to Tikhomirov's collection of Rare Book Department of State Public Scientific-Technological Library of the Siberian Branch of the RAS are considered, their decoration are analyzed.